ANALISIS FINANSIAL USAHA KECIL MENENGAH SIRUP MANGROVE DI KECAMATAN RANGSANG BARAT KEBUPATEN KEPULAUAN MERANTI - Siti Khoiriah; Rina Selva Johan; Fenny Trisnawati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: Meranti Islands District is one of the youngest in the Riau district, which has many UKM which one is mangrove syrup. Product development is a potential for a product that is still unique, and easy for obtaining the raw materials. Besides capital employed is still affordable by the peoples. Some factors of business is driving this effort, the authors is interested in conducting research on Financial Analysis of UKM Enterprises Syrup Mangrove in Meranti.The aim of this research was to determine whether the UKM enterprises syrup Meranti mangrove is viable when viewed from the financial aspects. The method is carried out to analyze the feasibility analysis investation by measuring the Net Present Value (NPV), Cost / Benefit Ratio (B/C Ratio), and Payback Period (PP). Based on the calculation of financial analysis of this mangrove fruit processing industry showed the Net Present Value (NPV) is Rp. 21,256,489. Therefore NPV is greater than zero, then the mangrove fruit processing industry are eligible to run. Value Benefit Cost Ratio (B / C Ratio) is equal to 2.04, as the B / C ratio is greater than one, the mangrove fruit processing industry are eligible to run. Payback Period of mangrove fruit processing industries are 1 year 1 month for entrepreneurs to get back the money that invested early in established businesses. From the results of the three studies above analysis method, it can be concluded that the mangrove fruit processing industry in the District of West Rangsang feasible.Keywords: Financial Analysis, Syrup Mangrove, Net Present Value, Benefit Cost Ratio and Payback Period